Penggunaan Wayground sebagai Media Pembelajaran Interaktif untuk Guru di Gugus VIII Bukik Saroban Kecamatan Lembah Gumanti Kabupaten Solok: Pengabdian - Nurfazlin Nova; Insyani, Nurdawani Putri; Widyawati, Siska; Lestari, Eka Puji; Sandi, Peki Fitra; hidayah, Zakiatun; Yunus, Yeni Sovia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Teachers play a crucial role in creating engaging and enjoyable learning by leveraging advances in media and technology to facilitate material delivery and student understanding. However, in several schools in Cluster VIII Bukik Saroban, Solok Regency, teachers still face difficulties in creating effective and innovative learning media due to limited technical skills, creativity, and understanding in adapting media to the material. The solution is ongoing training and mentoring through the Wayground platform, which is implemented in two sessions: a conceptual introduction and guided practice. The use of Wayground has been successful and received a positive response, resulting in increased student participation, ease of learning management, and improved student understanding and motivation to learn. Thus, this activity successfully bridges the demands of a student-centered curriculum with teachers' practical skills in the classroom.